Bonds not Claims. Political Representation as a form of Political Relationship - Zieliński, Mateusz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2024)
In the article, I argue that Michel Saward’s popular approach to political representation leads to its particularly problematic understanding as a potentially coercive form of political relationship. Drawing primarily on the experiences of feminist theorists, I argue that beyond analyzing the mechanism of ‘claim-making’, it is also ethically necessary to consider the possibilities and consequences of ‘claim-breaking’. Situations where political representation is broken illustrate how even institutionalized forms of representation often stem from the emotional needs of specific individuals, which politicians cynically exploit. To illustrate this, I utilize and critically assess Saward’s general explanatory model, analyzing the example of Donald Tusk’s resignation from the position of Prime Minister of Poland to assume the role of President of the European Council. W artykule wskazuję, że popularne podejście Michela Sawarda do reprezentacji politycznej prowadzi do jej wyjątkowo problematycznego ujęcia jako potencjalnie przemocowej formy relacji politycznej. Korzystając głównie z doświadczeń teoretyczek feministycznych, argumentuję, że poza analizą mechanizmu „tworzenia roszczeń” reprezentacji konieczne jest także etyczne rozważenie możliwości i konsekwencji „łamania roszczeń”. Sytuacje, w których reprezentacja polityczna jest zrywana, ilustrują, jak nawet zinstytucjonalizowane formy reprezentacji często mają korzenie w emocjonalnych potrzebach konkretnych ludzi, które politycy cynicznie wykorzystują. Aby to zobrazować, wykorzystuję i krytycznie oceniam ogólny model wyjaśniający Sawarda, analizując przykład rezygnacji Donalda Tuska z funkcji Premiera Polski, aby objąć stanowisko Przewodniczącego Rady Europejskiej.
Więzi, nie roszczenia. Reprezentacja polityczna jako forma relacji politycznej
Keywords: representative claim; political relationships; representation; roszczenie reprezentacyjne; relacje polityczne; reprezentacja